Textológiai megfontolások és poétikai tanulságok: (Fazekas Mihály: Lúdas Matyi) - Szilágyi, Márton (Studia Litteraria, 2020)
Mihály Fazekas’s epic poem was first published in 1815 without indicating the author; the author then intended to replace this “piratical edition”, published without his knowledge, with an authorised, revised edition, but still anonymously (1817). The article first discusses the philological questions of this publishing history with attention to the importance of textual modifications by the author. The study takes into consideration the questions surrounding the presumed source material’s origins known in international folklore, critically reviewing the standpoint of folkloristics and literary history so far. Then it concludes that it is not the title character of Lúdas Matyi who is the central figure, but the other important character, Döbrögi, because this latter one is capable of demonstrating the state of purity achieved through suffering, and Lúdas Matyi, who takes his revenge on him three times by beating him up, is only depicted as a means to that end. The article identifies the fundamental structural schemes of crime stories (Kriminalgeschichte) in the poetic solutions of the work, which genre became popular at the end of the 18th century-beginning of the 19th century, reaching Hungary via German intermediation in the 1810s.